Polypropylene film for printing and preparation method thereof

By using a multi-layer co-extruded polypropylene film structure and biaxial stretching process, the problems of high production cost and poor printability of film substrates have been solved, achieving high stiffness and high adhesion printing effect, and improving the service life and anti-counterfeiting properties of printed materials.

CN121043473APending Publication Date: 2025-12-02GUANGDONG ZHONGKE HUATONG NEW MATERIALS TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410686605.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-30
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing film substrates for printing are expensive to produce, and voids are easily formed within the substrate, leading to a decrease in the density, stiffness, and mechanical strength of the film substrate, resulting in poor printability. Furthermore, special irradiation treatments can affect the mechanical properties and service life of the material.

Method used

The film employs a multi-layer co-extruded polypropylene film structure. The printed layer contains polypropylene, polyethylene and their copolymers, and functional resins, while the main body layer contains homopolymer polypropylene. The bonding strength and stiffness are improved through biaxial stretching and corona treatment, and the coating steps are reduced to lower costs.

Benefits of technology

It achieves high whiteness, high opacity, and high stiffness in printing performance, improves the adhesion between printing ink and substrate, reduces production costs, and extends the service life and anti-counterfeiting properties of printed materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121043473A_ABST
    Figure CN121043473A_ABST
Patent Text Reader

Abstract

The invention discloses a polypropylene film for printing and a preparation method thereof.The polypropylene film comprises printing layers located on the upper surface layer and the lower surface layer and a main body layer clamped between the upper surface layer and the lower surface layer, and the components of the printing layers comprise one or more of polypropylene, polyethylene and copolymer thereof and functional resin; the main body layer comprises homo-polypropylene. Microscopic phase separation is formed in the processing process of polypropylene and polyethylene, so that a certain rough texture structure is formed on the surface, the interface interaction between printing ink and a base material can be increased, and the binding strength of the ink on the surface of the base material is remarkably improved; the polypropylene film has high whiteness, high covering power, high stiffness and printable performance, and the printing performance, the service life, the anti-counterfeiting characteristic and the liquidity of the securities, the currencies, the bills and the like made of the polypropylene film are superior to those of the securities, the currencies and the bills made of paper base materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of printed film technology, and more specifically, relates to a polypropylene film for printing and a method for preparing the same. Background Technology

[0002] Paper money is the most widely used form of currency in countries around the world today. In addition, there are promissory notes, checks, drafts, banknotes, and other forms of credit money, as well as other forms of negotiable instruments. Traditionally, all of these are printed using paper materials by specific departments authorized by the state. With the development of anti-counterfeiting technology, people have increasingly higher requirements for the lifespan, security, cleanliness, and resistance to counterfeiting of paper securities, currency, and negotiable instruments. Because plastic substrates can support more anti-counterfeiting technologies and have advantages such as high durability, high cleanliness, ease of automation, and environmental friendliness, they represent a major trend in future currency development.

[0003] To meet the special technical requirements of printing, anti-counterfeiting, etc., the production process of thin-film plastic securities, currency, and bills all require surface coating technology to obtain an opaque substrate before printing to obtain the final product. The coating process is complex, uses a variety of materials, and has high processing difficulty and precision control requirements. This results in a complex production process, low yield, and high production cost for securities, currency, and bills.

[0004] When plastic substrates are used as printing substrates for special purposes, they have certain drawbacks compared to traditional paper substrates. Paper materials have numerous fibrous capillary pores that can absorb ink, thus forming a strong bond. In contrast, plastic substrates are generally inert substances with essentially non-polar molecules and a very smooth surface that cannot absorb ink. This necessitates special surface modification of the plastic substrate or the addition of a printing primer to enhance the adhesion between the ink and the substrate.

[0005] Patent 201610262624.X developed a directly coatable polyolefin film and its preparation method. The film produced by this technology is obtained by subjecting the surface of the polyolefin material to low-temperature plasma treatment, while simultaneously introducing gaseous polar molecules to adjust the temperature and pressure for a gas-phase grafting reaction. It exhibits good printability and adhesion, and the surface polarity is effectively maintained, allowing for direct coating processing. ZL 201610262621.6 invented a biaxially oriented polymer film and its preparation method and application. The film produced by this technology is processed through a biaxial stretching process, featuring a three-layer structure. The matrix film layer, composed of olefin polymers, exhibits anisotropy, and the surface film layer, formed by multi-component copolymerized polyolefins, has a lower melting point than the matrix film layer. This film possesses high transparency, high rigidity and toughness, tear resistance, low-temperature resistance, and dimensional stability. 201610079590.0 provides a multilayer composite film with an XAYBX structure, its preparation method and application. The film produced by this technology has a five-layer structure with high surface polarity and uniform bidirectional mechanical properties. All three types of film plastics mentioned above require coating on a substrate first to give the substrate a specific opacity, and then special printing processing is performed, making the manufacturing process relatively complex.

[0006] Patent CN101160209A discloses a method for obtaining a 25-55 μm thick film with almost no surface unevenness by biaxially stretching an acrylic polymer with added inorganic compound powder. This invention gives the film uniform hiding power and excellent whiteness; however, the film cannot be directly used for special printing and requires surface modification and coating. Furthermore, during the stretching process, severe voiding occurs at the interface between the polymer matrix and the filler, resulting in a density of only 0.40–0.65 g / cm³. 3 This is far lower than the bulk density of polypropylene, which is 0.905 g / cm³. 3 This results in the film having insufficient stiffness, which cannot meet the requirements of subsequent special printing and processing techniques; at the same time, the thickness of this acrylic biaxially oriented film is too small, which is significantly different from the existing securities plastic substrates, affecting the subsequent special printing and processing.

[0007] Patent CN106397815A discloses a method for improving ink adhesion in plastic printed materials. This invention uses microwave radiation to oxidize the surface of the plastic product while simultaneously improving the ink formulation to enhance ink adhesion to the substrate. However, to achieve this, the film needs to be microwave-irradiated for 2-30 minutes in an oxidizing gas environment, which is time-consuming and inefficient. Furthermore, during microwave radiation, the polymer molecular chains undergo thermal degradation and ultraviolet radiation degradation, leading to a decrease in mechanical properties and shortening the lifespan and circulation time of the printed materials.

[0008] In summary, the production and preparation costs of film substrates currently used for printing are high, and voids are easily formed within the substrate, leading to a decrease in the density, stiffness, and mechanical strength of the film substrate. In addition, the printability of film substrates is poor. Even with special irradiation treatment to increase the adhesion of printing inks, the polymer materials will still degrade to some extent, affecting the service life of plastic printed products.

[0009] In view of this, the present invention is hereby proposed. Summary of the Invention

[0010] The purpose of this invention is to provide a polypropylene film for printing and a method for preparing the same, so as to reduce the production cost of the film substrate for printing, improve the stiffness and mechanical strength of the film, and increase the bonding strength between the printing ink and the polypropylene film.

[0011] To solve the above-mentioned technical problems, the basic concept of the technical solution adopted by the present invention is as follows:

[0012] A polypropylene film for printing includes a printing layer on an upper and a lower surface, and a main layer sandwiched between the upper and lower surface. The printing layer is composed of one or more of polypropylene, polyethylene and its copolymers, and functional resins. The main layer is composed of homopolymer polypropylene.

[0013] Furthermore, the functional resin in the printed layer includes one or more of the following: ethylene-to-higher α-olefin copolymer, propylene-to-higher α-olefin copolymer, cyclic olefin copolymer, cyclic olefin polymer, ethylene-acrylic acid copolymer, maleic anhydride-modified polypropylene, and maleic anhydride-modified polyethylene.

[0014] Preferably, the thickness of the printed layer is 1-3 μm, and the thickness of the main layer is 65 μm-100 μm.

[0015] Furthermore, the printed layer includes one or more of the following: homopolymer polypropylene, high-density polyethylene, ethylene-propylene-butene terpolymer, ethylene-propylene binary copolymer, propylene-butene binary copolymer, linear low-density polyethylene, and polyoxyethylene.

[0016] Preferably, the printed layer comprises linear low-density polyethylene and propylene-butene binary copolymer, or comprises ethylene-propylene-butene terpolymer and polyethylene oxide;

[0017] Preferably, the components of the printed layer further include anti-blocking masterbatch;

[0018] Preferably, the mass fraction of the anti-blocking masterbatch in the printed layer is 3-5%.

[0019] Furthermore, an adhesive layer is provided between the printed layer and the main body layer, and the components of the adhesive layer are selected from one or more of the following: ethylene-higher α-olefin copolymer, propylene-higher α-olefin copolymer, ethylene-propylene-butene terpolymer, and ethylene-propylene binary copolymer.

[0020] Furthermore, the main body layer also includes one or more of the following: nucleating agent masterbatch, ultraviolet absorber masterbatch, titanium dioxide masterbatch, calcium carbonate masterbatch, barium sulfate needle-shaped masterbatch, lithopone masterbatch, ultrafine talc masterbatch, and titanyl sulfide masterbatch.

[0021] Furthermore, the polypropylene film has an opacity of 10-90%, a stiffness of 80-90 mN.m in the longitudinal direction and 160-210 mN.m in the transverse direction, and a heat shrinkage rate of ≤3% in the longitudinal direction and ≤3% in the transverse direction.

[0022] Preferably, the polypropylene film has an opacity of 10-90%, a whiteness of 10-90%, and a surface tension of 36-44 dyn / cm. The present invention also provides a method for preparing a polypropylene film for printing as described in any of the above technical solutions, comprising:

[0023] (1) The raw materials of each layer of polypropylene film are transported to the extruder, heated and mixed to form a melt; the melt is transported to the die head through the pipeline, flows out through the die head, and is cooled to form a thick sheet;

[0024] (2) The thick sheet is biaxially stretched and then subjected to high-temperature annealing to form a biaxially stretched film.

[0025] (3) The biaxially oriented membrane is subjected to corona treatment to achieve a surface energy of 40 dyn / cm or higher, with a corona power of 30-40 Wmin / m. 2 ;

[0026] (4) The biaxially stretched membrane is subjected to a second heat treatment to obtain the final product.

[0027] Furthermore, in step (2), bidirectional stretching is performed simultaneously, or longitudinal stretching is performed first and then transverse stretching is performed.

[0028] Further, step (2) includes: drawing the thick sheet to the longitudinal stretching unit, subjecting it to heat treatment by 8-14 sets of preheating rollers to soften the thick sheet, with the temperature of the preheating rollers being 80-135℃; stretching the softened thick sheet to 3-6 times its original size to form a unidirectional stretched sheet, with the temperature of the stretching rollers being 100-130℃; and performing high-temperature annealing on the unidirectional stretched sheet, with the annealing temperature being 125-145℃.

[0029] The uniaxially stretched sheet is drawn to the transverse stretching unit and preheated at 160-180℃ to soften the film; then it is stretched at 150-160℃ with a stretching ratio of 6-9 times to form a biaxially stretched film; the transversely stretched film is then subjected to high-temperature annealing, with the annealing temperature set in the range of 145-165℃.

[0030] Further, step (2) includes: drawing the thick sheet to the stretching unit and preheating it at 160-180°C; then using a fixture and track design, stretching the film simultaneously in the longitudinal and transverse directions, with a longitudinal stretching ratio of 3-6 times and a transverse stretching ratio of 6-9 times, to form a biaxially stretched film at a stretching temperature of 150-165°C; and subjecting the biaxially stretched film to high-temperature annealing treatment at a temperature set in the range of 145-165°C.

[0031] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art.

[0032] The polypropylene film used for printing in this invention has high whiteness, high opacity, high stiffness, and printability. Securities, currency, and bills prepared using the product of this invention have better printing performance, service life, anti-counterfeiting characteristics, and circulation than those prepared using paper substrates.

[0033] This invention significantly improves the adhesion between printing ink and the polypropylene film substrate by adding a highly polar polymer material to the surface layer of a multilayer co-extruded polypropylene film. Furthermore, by adding a filler to the main layer to enhance opacity, this invention imparts suitable opacity to the substrate, replacing the opaque coating in traditional processes, reducing one processing step, and effectively lowering processing costs.

[0034] This invention improves the crystallinity of polypropylene by adding a post-curing process, which relaxes the oriented molecular chains and effectively improves the various physical properties of the polypropylene film substrate, especially the heat resistance and stiffness of the substrate. At the same time, the main layer of the multilayer co-extruded polypropylene film contains anisotropic functional fillers, and the anisotropic fillers are oriented along the stretching direction by using a biaxial stretching process.

[0035] This invention adjusts the composition of the printing layer formula, utilizing the micro-phase separation formed by polypropylene and polyethylene during processing to create a certain rough textured structure on its surface. This increases the interfacial interaction between the printing ink and the substrate, significantly improving the adhesion of the ink to the substrate surface.

[0036] The specific embodiments of the present invention will be described in further detail below. Attached Figure Description

[0037] The accompanying drawings, as part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention, but do not constitute an undue limitation of the invention. Obviously, the drawings described below are merely some embodiments, and those skilled in the art can obtain other drawings based on these drawings without creative effort. In the drawings:

[0038] Figure 1 This is a schematic diagram of the three-layer co-extruded film structure of the present invention;

[0039] Figure 2 This is a schematic diagram of the structure of the five-layer co-extruded film of the present invention.

[0040] In the picture:

[0041] 1. Top layer; 2. Main layer; 3. Bottom layer; 4. Top adhesive layer; 5. Bottom adhesive layer. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below. The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0043] The raw materials used in the embodiments of this invention are shown in Table 1 below;

[0044] Table 1:

[0045]

[0046] Example 1

[0047] This embodiment provides a method for preparing a polypropylene film, including:

[0048] (1) Different raw materials are fed to the extruder in a certain proportion using the feeding system. The extruder heats and mixes the materials to form a melt. The melt is then transported to the die through a pipeline and flows out through the die. The melt is cooled immediately after exiting the die to form a thick sheet. The cooling temperature is set between 15-50℃ and adjusted according to the production process.

[0049] (2) The thick sheet formed in step (1) is drawn to the longitudinal stretching unit. First, it is heat-treated by 8-14 sets of preheating rollers to soften the thick sheet. The temperature setting range of the preheating rollers is 80-135℃. Then, using 6 sets of stretching rollers, the softened thick sheet is stretched to 3-6 times to form a unidirectional stretching sheet. The temperature setting value of the stretching rollers is 100-130℃. The unidirectional stretching film is subjected to high-temperature annealing treatment to partially relax the oriented molecular chains. The annealing temperature setting range is 125-145℃.

[0050] The uniaxially stretched film is drawn into the transverse stretching unit, where it is first preheated at 160-180℃ to soften it. Then it is stretched at 150-160℃ with a stretching ratio of 6-9 times to form a biaxially stretched film. After the transversely stretched film is completed, it needs to undergo high-temperature annealing to partially relax the oriented molecular chains. The annealing temperature is set within the range of 145-165℃.

[0051] (3) The biaxially oriented membrane is subjected to corona treatment to achieve a surface energy of 40 dyn / cm or higher. The corona power is set at 30-40 Wmin / m. 2 The corona-treated film meets printing requirements. The heat-treated film is then wound up and slit to form intermediate products.

[0052] (4) The biaxially stretched membrane is subjected to a secondary heat treatment to further stabilize its microstructure. The secondary heat treatment can be performed online or offline.

[0053] Example 2

[0054] This embodiment provides a method for preparing a polypropylene film, including:

[0055] (1) Different raw materials are fed to the extruder in a certain proportion using the feeding system. The extruder heats and mixes the materials to form a melt. The melt is then transported to the die through a pipeline and flows out through the die. The melt is cooled immediately after exiting the die to form a thick sheet. The cooling temperature is set between 15-50℃ and adjusted according to the production process.

[0056] (2) The thick sheet is pulled to the stretching unit and preheated at 160-180℃; then, using the fixture and track design, the film is stretched in both the longitudinal and transverse directions at the same time. The longitudinal stretching ratio is 3-6 times and the transverse stretching ratio is 6-9 times to form a biaxially stretched film. The stretching temperature is 150-165℃. The biaxially stretched film is subjected to high-temperature annealing treatment. The annealing temperature is set in the range of 145-165℃.

[0057] (3) The biaxially oriented membrane is subjected to corona treatment to achieve a surface energy of 40 dyn / cm or higher. The corona power is set at 30-40 Wmin / m. 2 The corona-treated film meets printing requirements. The heat-treated film is then wound up and slit to form intermediate products.

[0058] (4) The biaxially stretched membrane is subjected to a secondary heat treatment to further stabilize its microstructure. The secondary heat treatment can be performed online or offline.

[0059] Example 3

[0060] This embodiment uses the polypropylene film preparation method of Example 1 to prepare the film. This embodiment provides a three-layer co-extruded biaxially oriented film, such as... Figure 1 As shown, its main structure includes two upper surface layers and a main body layer sandwiched between the two surface layers, wherein:

[0061] The upper layer 1, the main corona surface, is 2 μm thick and, by mass fraction, includes: 95% propylene-ethylene-butene terpolymer polypropylene and 5% silica masterbatch, with silica in the silica masterbatch having a mass fraction of 3%.

[0062] The lower surface layer 3, the secondary corona surface, is 2 μm thick and, by mass fraction, comprises: 95% propylene-ethylene-butene terpolymer polypropylene and 5% silica masterbatch, with silica masterbatch containing 3% silica by mass.

[0063] Main layer 2, 90µm thick, contains 90% homopolymer polypropylene and 10% titanium dioxide masterbatch by mass fraction, with titanium dioxide comprising 70% by mass fraction in the titanium dioxide masterbatch.

[0064] Example 4:

[0065] A three-layer co-extruded biaxially oriented film, such as Figure 1 As shown, its main structure includes two upper surface layers and a main body layer sandwiched between the two surface layers, wherein:

[0066] The upper layer 1, the main corona surface, has a thickness of 2 μm and, by mass fraction, includes: 40% propylene-butene binary copolymer polypropylene, 40% high-density polyethylene, 15% propylene-ethylene-butene terpolymer polypropylene, and 5% silica masterbatch, in which the mass fraction of silica in the silica masterbatch is 3%.

[0067] The lower layer 3, the secondary corona surface, is 2 μm thick and, by mass fraction, includes: 40% propylene-butene binary copolymer polypropylene, 40% high-density polyethylene, 15% linear low-density polyethylene, and 5% silica masterbatch, with silica comprising 3% by mass in the silica masterbatch.

[0068] The main layer 2, with a thickness of 90 μm, comprises, by mass fraction: 85% homopolymer polypropylene, 10% titanium dioxide masterbatch, and 5% acicular wollastonite masterbatch; the titanium dioxide masterbatch contains 70% titanium dioxide by mass, and the acicular wollastonite masterbatch contains 60% wollastonite by mass.

[0069] Example 5:

[0070] A three-layer co-extruded biaxially oriented film, such as Figure 1 As shown, its main structure includes two upper surface layers and a main body layer sandwiched between the two surface layers, wherein:

[0071] The upper surface layer 1, the main corona surface, has a thickness of 2 μm and, by mass fraction, includes: 50% propylene-butene binary copolymer polypropylene, 40% high-density polyethylene, 5% ethylene-methyl acrylate copolymer (EMA), and 5% silica masterbatch, with the silica masterbatch containing 3% silica by mass.

[0072] The lower surface layer 3, the secondary corona surface, is 2 μm thick and, by mass fraction, comprises: 50% propylene-butene binary copolymer polypropylene, 40% high-density polyethylene, 5% ethylene-butyl acrylate copolymer (EBA), and 5% silica masterbatch, with silica comprising 3% by mass in the silica masterbatch.

[0073] Main layer 2, 90µm thick, comprises by mass fraction: 85% homopolymer polypropylene, 12% titanium dioxide masterbatch, and 3% calcium carbonate masterbatch. The titanium dioxide masterbatch contains 70% titanium dioxide by mass, and the calcium carbonate masterbatch contains 80% calcium carbonate by mass.

[0074] Example 6:

[0075] A three-layer co-extruded biaxially oriented film, such as Figure 1 As shown, its main structure includes two upper surface layers and a main body layer sandwiched between the two surface layers, wherein:

[0076] The upper layer 1, the main corona surface, has a thickness of 2 μm and, by mass fraction, includes: 42.5% propylene-butene binary copolymer polypropylene, 42.5% high-density polyethylene, 5% propylene-ethylene-butene terpolymer polypropylene, 5% maleic anhydride modified polypropylene, and 5% silica masterbatch, wherein the silica masterbatch contains 5% silica by mass.

[0077] The lower surface layer 3, the secondary corona surface, is 2 μm thick and, by mass fraction, comprises: 42.5% propylene-butene binary copolymer polypropylene, 42.5% high-density polyethylene, 5% propylene-ethylene-butene terpolymer polypropylene, 5% maleic anhydride modified linear low-density polyethylene, and 5% silica masterbatch, wherein the silica masterbatch contains 5% silica by mass.

[0078] The main layer 2, with a thickness of 90 μm, comprises 83% homopolymer polypropylene, 12% titanium dioxide masterbatch, and 5% acicular wollastonite masterbatch by mass fraction. The titanium dioxide masterbatch contains 70% titanium dioxide by mass, and the acicular wollastonite masterbatch contains 80% wollastonite by mass fraction.

[0079] Example 7:

[0080] A three-layer co-extruded biaxially oriented film, such as Figure 1As shown, its main structure includes two upper surface layers and a main body layer sandwiched between the two surface layers, wherein:

[0081] The upper layer 1, the main corona surface, is 2 μm thick and, by mass fraction, includes: 50% propylene-butene binary copolymer polypropylene, 40% high-density polyethylene, 7% cyclic polyolefin (COC), and 3% silica masterbatch, in which the mass fraction of silica in the silica masterbatch is 3%.

[0082] The lower surface layer 3, the secondary corona surface, is 2 μm thick and, by mass fraction, includes: 40% propylene-butene binary copolymer polypropylene, 40% high-density polyethylene, 15% cyclic polyolefin (COC), and 5% silica masterbatch, with the silica masterbatch containing 3% silica by mass.

[0083] The main layer 2, with a thickness of 90 μm, comprises, by mass fraction: 83% homopolymer polypropylene, 12% titanium dioxide masterbatch, and 5% nucleating agent masterbatch. The titanium dioxide masterbatch contains 70% titanium dioxide by mass, and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0084] Example 8:

[0085] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and a main body layer 2 sandwiched between the two secondary upper surface layers, wherein:

[0086] Upper surface layer 1, main corona surface, thickness 2um, the raw materials and their proportions are the same as those of upper surface layer 1 in Example 7;

[0087] The lower surface layer 3, the secondary corona surface, has a thickness of 2 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 7.

[0088] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 70% propylene-butene binary copolymer polypropylene, 25% propylene and advanced α-olefin copolymer, and 5% titanium dioxide masterbatch, wherein the titanium dioxide masterbatch contains 70% titanium dioxide by mass.

[0089] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 70% propylene-butene binary copolymer polypropylene, 25% propylene and advanced α-olefin copolymer, and 5% titanium dioxide masterbatch, wherein the mass fraction of titanium dioxide in the titanium dioxide masterbatch is 70%.

[0090] Main layer 2, 86µm thick, provides stiffness and opacity, and by mass fraction comprises: 88% homopolymer polypropylene and 12% by weight titanium dioxide masterbatch, in which titanium dioxide accounts for 70% by mass.

[0091] Example 9:

[0092] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and an inner surface layer sandwiched between the two secondary upper surface layers, wherein:

[0093] Upper surface layer 1, main corona surface, thickness 2um, the raw materials and their proportions are the same as those of upper surface layer 1 in Example 4;

[0094] The lower surface layer 3, the secondary corona surface, has a thickness of 2 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 4.

[0095] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 70% propylene-butene binary copolymer, 25% propylene and advanced α-olefin copolymer, and 5% titanate masterbatch, wherein the titanate masterbatch contains 70% titanate by mass fraction.

[0096] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 70% propylene-butene binary copolymer, 25% propylene and advanced α-olefin copolymer, and 5% titanate masterbatch, wherein the titanate masterbatch contains 70% titanate by mass fraction.

[0097] Main layer 2, 86µm thick, provides opacity and rigidity, and by mass fraction comprises: 85% homopolymer polypropylene, 10% titanium dioxide masterbatch, and 5% nucleating agent masterbatch, wherein the titanium dioxide masterbatch contains 70% titanium dioxide by mass and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0098] Example 10:

[0099] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and an inner surface layer sandwiched between the two secondary upper surface layers, wherein:

[0100] Upper surface layer 1, main corona surface, thickness 2um, the raw materials and their proportions are the same as those of upper surface layer 1 in Example 6;

[0101] The lower surface layer 3, the secondary corona surface, has a thickness of 2 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 6.

[0102] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 65% propylene-butene binary copolymer, 30% propylene and advanced α-olefin copolymer, and 5% titanium dioxide masterbatch, wherein the titanium dioxide masterbatch contains 70% titanium dioxide by mass.

[0103] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 70% propylene-butene binary copolymer polypropylene, 25% propylene and advanced α-olefin copolymer, and 5% titanium dioxide masterbatch, wherein the titanium dioxide masterbatch contains 70% titanium dioxide by mass.

[0104] The main layer 2, with a thickness of 86 μm, provides opacity and rigidity, and by mass fraction comprises: 80% homopolymer polypropylene, 10% titanium dioxide masterbatch, 5% talc masterbatch, and 5% nucleating agent masterbatch; the titanium dioxide masterbatch contains 70% titanium dioxide by mass, the talc masterbatch contains 50% talc by mass, and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0105] Example 11:

[0106] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and an inner surface layer sandwiched between the two secondary upper surface layers, wherein:

[0107] The upper surface layer 1, the main corona surface, has a thickness of 2 μm. The raw materials and their proportions used are the same as those for the upper surface layer 1 in Example 5.

[0108] The lower surface layer 3, the secondary corona surface, has a thickness of 2 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 5.

[0109] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 70% propylene-butene binary copolymer polypropylene, 25% ethylene-acrylic acid copolymer (EAA), and 5% zinc oxide masterbatch, wherein the zinc oxide masterbatch contains 40% zinc oxide by mass fraction.

[0110] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 75% propylene-butene binary copolymer polypropylene, 20% ethylene-ethyl acrylate copolymer (EEA), and 5% lithopone masterbatch, wherein the lithopone masterbatch contains 50% lithopone by mass.

[0111] Main layer 2, 86µm thick, provides opacity and rigidity, and by mass fraction comprises: 83% homopolymer polypropylene, 12% titanium dioxide masterbatch, and 5% nucleating agent masterbatch, wherein the titanium dioxide masterbatch contains 70% titanium dioxide by mass and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0112] Example 12:

[0113] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and an inner surface layer sandwiched between the two secondary upper surface layers, wherein:

[0114] Upper surface layer 1, main corona surface, thickness 2um, the raw materials and their proportions are the same as those of upper surface layer 1 in Example 3;

[0115] The lower surface layer 3, the secondary corona surface, has a thickness of 2 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 3.

[0116] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 2 μm. The raw materials and their proportions are the same as those used in the upper adhesive layer 4 of Example 9.

[0117] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 2 μm. The raw materials and their proportions are the same as those used in the lower adhesive layer 5 of Example 9.

[0118] Main layer 2, 86µm thick, provides opacity and rigidity, and by mass fraction comprises: 80% homopolymer polypropylene, 10% titanium dioxide masterbatch, 5% titania sulfide masterbatch, and 5% nucleating agent masterbatch. The titanium dioxide masterbatch contains 70% titanium dioxide by mass, the titania sulfide masterbatch contains 40% titania sulfide by mass, and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0119] Example 13

[0120] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and an inner surface layer sandwiched between the two secondary upper surface layers, wherein:

[0121] Upper surface layer 1, main corona surface, thickness 1µm, uses the same raw materials and proportions as upper surface layer 1 in Example 3;

[0122] The lower surface layer 3, the secondary corona surface, has a thickness of 1 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 3.

[0123] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 1 μm, and by mass fraction comprises: 70% ethylene-advanced α-olefin copolymer, 25% ethylene-propylene-butene terpolymer, and 5% zinc oxide masterbatch, wherein the zinc oxide masterbatch contains 40% zinc oxide by mass fraction.

[0124] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 1 μm, and by mass fraction comprises: 70% ethylene-advanced α-olefin copolymer, 25% ethylene-propylene-butene terpolymer, and 5% zinc oxide masterbatch, wherein the zinc oxide masterbatch contains 40% zinc oxide by mass fraction.

[0125] Main layer 2, 65µm thick, provides opacity and rigidity, and by mass fraction comprises: 80% homopolymer polypropylene, 10% titanium dioxide masterbatch, 5% titania sulfide masterbatch, and 5% nucleating agent masterbatch. The titanium dioxide masterbatch contains 70% titanium dioxide by mass, the titania sulfide masterbatch contains 40% titania sulfide by mass, and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0126] Example 14

[0127] A five-layer co-extruded biaxially oriented film, such as Figure 2 As shown, its main structure includes two upper surface layers, two secondary upper surface layers, and an inner surface layer sandwiched between the two secondary upper surface layers, wherein:

[0128] The upper surface layer 1, the main corona surface, has a thickness of 3 μm. The raw materials and their proportions used are the same as those in the upper surface layer 1 of Example 3.

[0129] The lower surface layer 3, the secondary corona surface, has a thickness of 3 μm. The raw materials and their proportions used are the same as those in the lower surface layer 3 of Example 3.

[0130] The upper adhesive layer 4 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 75% ethylene-advanced α-olefin copolymer, 20% ethylene-propylene-butene terpolymer, and 5% zinc oxide masterbatch, wherein the zinc oxide masterbatch contains 40% zinc oxide by mass fraction.

[0131] The lower adhesive layer 5 provides opacity and interlayer adhesion, with a thickness of 2 μm, and by mass fraction comprises: 75% ethylene-advanced α-olefin copolymer, 20% ethylene-propylene-butene terpolymer, and 5% zinc oxide masterbatch, wherein the zinc oxide masterbatch contains 40% zinc oxide by mass fraction.

[0132] Main layer 2, 100µm thick, provides opacity and rigidity, and by mass fraction comprises: 80% homopolymer polypropylene, 10% titanium dioxide masterbatch, 5% titania sulfide masterbatch, and 5% nucleating agent masterbatch. The titanium dioxide masterbatch contains 70% titanium dioxide by mass, the titania sulfide masterbatch contains 40% titania sulfide by mass, and the nucleating agent masterbatch contains 10% nucleating agent by mass.

[0133] Experimental Example 1

[0134] This experiment tested the properties of the films from Examples 3 to 12. The stiffness of the films was measured using a stiffness meter; the Young's modulus and yield strength of the films reflected their flexibility; lower Young's modulus and yield strength indicated better film flexibility. In this invention, the stiffness of the films was characterized by measuring the bending stiffness of the samples; the measurement method followed GB / T23144-2008, and specific data are shown in Table 2. The data in the table are the average values ​​of the test data after aging. After prolonged aging treatment, the stiffness of the films will change due to changes in the aggregated microstructure.

[0135] The opacity of the film can be measured using a whiteness meter, following the method specified in GB / T 1543-2005 "Determination of Opacity (Paper Backing) of Paper and Paperboard (Diffuse Reflection Method)". Specific data are shown in Table 2. The heat resistance of the film has a significant impact on printing and processing; it is generally characterized by a heat shrinkage test. During development, the heat resistance of the film was tested according to GB / T10003-2008 "General Purpose Biaxially Oriented Polypropylene (BOPP) Film". Specific data are shown in Table 2. The optical appearance and surface properties of the film have a significant impact on its printing effect. During development, ink adhesion was tested according to GB / T 13217.7-2023 "Ink Adhesion Test Method". Specific data are shown in Table 3.

[0136] Table 2:

[0137]

[0138] Table 3:

[0139] Example Gloss (%) Surface tension (mN) Ink adhesion Example 3 89.5 42 Level 0 Example 4 27.5 44 Level 0 Example 5 32.5 44 Level 0 Example 6 9.7 42 Level 0 Example 7 17.9 44 Level 0 Example 8 19.5 44 Level 0 Example 9 18.9 42 Level 0 Example 10 9.8 40 Level 0 Example 11 13.5 46 Level 0 Example 12 88.2 44 Level 0

[0140] As shown in Table 2 above, the opacity of the polypropylene film in this invention is 55.4-90.5%, and higher opacity means the film has better light-blocking properties. The stiffness is 112-136 mN.m in the longitudinal direction and 212-238 mN.m in the transverse direction. Higher stiffness means the film has better rigidity and bending resistance under stress, which helps maintain the shape and structural integrity of the film. The heat shrinkage rate is ≤2.4% in the longitudinal direction and ≤0.45% in the transverse direction. Lower heat shrinkage rate means the film deforms less when heated, exhibiting better thermal and dimensional stability.

[0141] As shown in Table 3 above, the ink adhesion of the polypropylene film in this invention is grade 0, which means that the bond between the ink and the film is very strong, contributing to improved print quality and durability. Furthermore, the gloss of the polypropylene film can be adjusted between 9.7% and 89.5%. When the gloss is less than 30%, its surface exhibits a matte texture. This texture typically produces a soft, uniform light reflection effect, avoiding strong glare and reducing interference from reflected light. This matte texture effectively reduces light reflection and refraction, thereby reducing specular reflection and allowing observers to more easily observe details of patterns or text without significant interference, improving visual appeal. In addition, lower gloss also makes colors more saturated and realistic, increasing visual comfort and perceived quality.

[0142] Experimental Example 2

[0143] This experimental example provides a verification process for the influence of the composition of the printed layer on the performance of polypropylene films;

[0144] This experimental group is a further test group based on Example 3. The only difference between each experimental group and Example 3 is the composition of the printed layer (upper and lower surface layers), as shown in Table 4 below:

[0145] Table 4:

[0146]

[0147]

[0148] As can be seen from test group 1, the ink adhesion strength of homopolymer polypropylene in the test was poor, reaching level 5; this indicates that when homopolymer polypropylene is used as a single material, its surface has weak adhesion to ink, which easily leads to ink peeling or poor adhesion.

[0149] The film in test group 11 consisted of 100% ethylene-propylene-butadiene terpolymer polypropylene (upper surface layer 1, lower surface layer 3), 90% homopolymer polypropylene, and 10% titanium dioxide masterbatch (main body layer 2), with an ink adhesion strength of grade 1. The film in test group 12 consisted of 70% ethylene-propylene-butadiene terpolymer polypropylene, 30% polyethylene oxide (upper surface layer 1, lower surface layer 3), 90% homopolymer polypropylene, and 10% titanium dioxide masterbatch (main body layer 2), with an ink adhesion strength of grade 0 (best). It is evident that the film in test group 11, with an ink adhesion strength of grade 1, performed relatively well, but not as well as the mixed materials that achieved grade 0; the film in test group 12 achieved an ink adhesion strength of grade 0, demonstrating the best performance. This indicates that the mixture of ethylene-propylene-butadiene terpolymer polypropylene and polyethylene oxide can significantly improve ink adhesion strength.

[0150] In other words, ethylene-propylene-butadiene terpolymer polypropylene (TPP) performs well in terms of ink adhesion, especially when mixed with polyethylene oxide, it can achieve the best ink adhesion (grade 0). Pure ethylene-propylene-butadiene terpolymer polypropylene (100%) has an ink adhesion grade of 1, which is not as good as the mixed materials, but it is still better than single homopolymer polypropylene and high-density polyethylene.

[0151] Furthermore, a comparison of test groups 2, 3, 4, 5, 8, 9, and 10 shows that the ink adhesion fastness of propylene-butadiene binary copolymer polypropylene (PP-B) itself is grade 3. After mixing with high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE), the ink adhesion fastness is significantly improved, especially in the case of 50% PP-B and 50% HDPE or LLDPE, achieving the optimal grade 0 ink adhesion fastness.

[0152] A comparison of test groups 3, 4, 5, and 6 shows that the ink adhesion fastness of pure high-density polyethylene is grade 5, which is poor. However, when mixed with propylene-butadiene binary copolymer polypropylene, especially when mixed in equal proportions (50% HDPE, 50% PP-B), the ink adhesion fastness significantly improves to grade 0.

[0153] A comparison of test groups 7, 8, and 9 shows that pure linear low-density polyethylene exhibits the best ink adhesion fastness, with a grade of 0. When mixed with propylene-butadiene binary copolymer polypropylene, it also maintains the best ink adhesion fastness (grade 0).

[0154] In summary, propylene-butadiene copolymer polypropylene (PP-B) has an ink adhesion strength of grade 3 on its own. When mixed with HDPE or LLDPE, the strength is significantly improved, reaching grade 0 at a mixing ratio of 50%. Pure HDPE has a relatively poor ink adhesion strength (grade 5), but when mixed with PP-B, especially at a 50% mixing ratio, the ink adhesion strength significantly improves to grade 0. Linear low-density polyethylene (LLDPE) has the best ink adhesion strength on its own (grade 0), and even after mixing with PP-B, it maintains the best ink adhesion strength (grade 0). Therefore, mixing PP-B with HDPE or LLDPE can significantly improve ink adhesion strength, especially with LLDPE. HDPE needs to be mixed with PP-B to improve ink adhesion strength, while LLDPE itself has the best ink adhesion strength and can be used as a primary material for improving the ink adhesion performance of films.

[0155] Experimental Example 3

[0156] This experimental example provides a verification process for the effect of the type and amount of polyethylene added in the printed layer on the film performance. This experimental example is a further experimental group set up based on Example 3. The only difference between each experimental group and Example 3 is the composition of the printed layer (upper and lower surface layers), as shown in Table 5 below:

[0157] Table 5:

[0158]

[0159] Gloss reflects the smoothness of the surface. The higher content of linear low-density polyethylene in test groups 4 and 5 resulted in a smoother film surface and higher gloss. Haze indicates the transparency of the film. The type and amount of polyethylene added in test groups 4 and 5 resulted in less internal scattering, thus reducing haze.

[0160] Compared to Experimental Group 2, Experimental Group 1 contained the same type of polyethylene, but in different proportions. Experimental Group 1 had a higher content of high-density polyethylene, resulting in a smoother surface and higher gloss. In contrast, Experimental Group 2 had a lower content of high-density polyethylene, resulting in poorer gloss and higher haze.

[0161] Compared to test groups 3, 4, and 5, test group 3 had a higher content of high-density polyethylene, resulting in relatively lower gloss and higher haze. In contrast, the linear low-density polyethylene in test groups 4 and 5 resulted in higher film gloss and lower haze.

[0162] To improve the appearance and transparency of the film, combinations with lower linear low-density polyethylene content, such as those in experimental groups 4 and 5, can be considered. Further optimization could involve adjusting the type and amount of polyethylene added to balance gloss and haze, achieving more ideal performance.

[0163] Test Example 4

[0164] This experimental example provides a verification process for the influence of the adhesive layer on the performance of a polypropylene film with a multilayer structure, where the core layer is the main raw material. If too much polyethylene material is added to the surface layer, it will lead to insufficient bonding between the surface layer and the core layer, resulting in delamination during peel tests when laminated with other films. This experiment utilizes a five-layer co-extrusion apparatus to add this surface layer between the surface layer and the core layer, thereby increasing the bonding strength between them.

[0165] Specifically, this experimental example is a further experimental group set up based on Example 3, as shown in Table 6 below:

[0166] Table 6:

[0167]

[0168] The results above show that adding a large amount of HDPE to the surface layer formulation makes interlayer separation between the surface and core layers more likely. To address this issue, a sub-surface layer can be added to increase the bonding strength between the surface and core layers. When a binary copolymer and POE (ethylene / α-olefin copolymer) are used as the sub-surface layer, the interlayer bonding is significantly improved.

[0169] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-described technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A polypropylene film for printing, characterized in that: It includes a printing layer located on the upper and lower surfaces, and a main body layer sandwiched between the upper and lower surfaces. The printing layer is composed of one or more of polypropylene, polyethylene and its copolymers, and functional resins. The main body layer is composed of homopolymer polypropylene.

2. The polypropylene film for printing according to claim 1, characterized in that: The functional resins in the printed layer include one or more of the following: ethylene-to-higher α-olefin copolymers, propylene-to-higher α-olefin copolymers, cyclic olefin copolymers, cyclic olefin polymers, ethylene-acrylic acid copolymers, maleic anhydride-modified polypropylene, and maleic anhydride-modified polyethylene. Preferably, the thickness of the printed layer is 1-3 μm, and the thickness of the main layer is 65 μm-100 μm.

3. A polypropylene film for printing according to claim 1 or 2, characterized in that: The printed layer includes one or more of the following: homopolymer polypropylene, high-density polyethylene, ethylene-propylene-butene terpolymer, ethylene-propylene binary copolymer, propylene-butene binary copolymer, linear low-density polyethylene, and polyoxyethylene. Preferably, the printed layer comprises linear low-density polyethylene and propylene-butene binary copolymer, or comprises ethylene-propylene-butene terpolymer and polyethylene oxide; Preferably, the components of the printed layer further include anti-blocking masterbatch; Preferably, the mass fraction of the anti-blocking masterbatch in the printed layer is 3-5%.

4. A polypropylene film for printing according to any one of claims 1-3, characterized in that: An adhesive layer is also provided between the printed layer and the main body layer. The adhesive layer is composed of one or more of the following: ethylene-higher α-olefin copolymer, propylene-higher α-olefin copolymer, ethylene-propylene-butene terpolymer, ethylene-propylene binary copolymer, propylene-butene binary copolymer, ethylene-acrylic acid copolymer, and ethylene-ethyl acrylate copolymer.

5. A polypropylene film for printing according to any one of claims 1-4, characterized in that: The main body layer also includes one or more of the following: nucleating agent masterbatch, ultraviolet absorber masterbatch, titanium dioxide masterbatch, calcium carbonate masterbatch, barium sulfate needle-shaped masterbatch, lithopone masterbatch, ultrafine talc masterbatch, and titanium dioxide masterbatch.

6. A polypropylene film for printing according to any one of claims 1-5, characterized in that: The polypropylene film has an opacity of 10-90%, a stiffness of 80-90 mN.m in the longitudinal direction and 160-210 mN.m in the transverse direction, and a heat shrinkage rate of ≤3% in the longitudinal direction and ≤3% in the transverse direction. Preferably, the polypropylene film has an opacity of 10-90%, a whiteness of 10-90%, and a surface tension of 36-44 dyn / cm.

7. A method for preparing a polypropylene film for printing as described in any one of claims 1-6, characterized in that: (1) The raw materials of each layer of polypropylene film are transported to the extruder, heated and mixed to form a melt; the melt is transported to the die head through the pipeline, flows out through the die head, and is cooled to form a thick sheet; (2) The thick sheet is biaxially stretched and then subjected to high-temperature annealing to form a biaxially stretched film. (3) The biaxially stretched diaphragm is subjected to corona treatment to make its surface energy reach more than 40 dyn / cm, and the corona power is 30-40 Wmin / m2. (4) The biaxially stretched membrane is subjected to a second heat treatment to obtain the final product.

8. The method for preparing a polypropylene film for printing according to claim 7, characterized in that: In step (2), bidirectional stretching is performed simultaneously, or longitudinal stretching is performed first and then transverse stretching is performed.

9. The method for preparing a polypropylene film for printing according to claim 8, characterized in that: Step (2) includes: drawing the thick sheet to the longitudinal stretching unit, and heat-treating it through 8-14 sets of preheating rollers to soften the thick sheet, with the temperature of the preheating rollers being 80-135℃; stretching the softened thick sheet to 3-6 times its original size to form a unidirectional stretched sheet, with the temperature of the stretching rollers being 100-130℃; and performing high-temperature annealing on the unidirectional stretched sheet, with the annealing temperature being 125-145℃. The uniaxially stretched sheet is drawn to the transverse stretching unit and preheated at 160-180℃ to soften the film; then it is stretched at 150-160℃ with a stretching ratio of 6-9 times to form a biaxially stretched film; the transversely stretched film is then subjected to high-temperature annealing, with the annealing temperature set in the range of 145-165℃.

10. The method for preparing a polypropylene film for printing according to claim 8, characterized in that: Step (2) includes: drawing the thick sheet to the stretching unit and preheating it at 160-180°C; then using the fixture and track design, stretching the film simultaneously in the longitudinal and transverse directions, with a longitudinal stretching ratio of 3-6 times and a transverse stretching ratio of 6-9 times to form a biaxially stretched film, with a stretching temperature of 150-165°C; and subjecting the biaxially stretched film to high-temperature annealing treatment, with the annealing temperature set in the range of 145-165°C.

Citation Information

Patent Citations

  • Biaxially stretched multilayer polypropylene film and use thereof

    CN101160209A

  • Directly coated polyolefin film and preparation method thereof

    CN105820365A

  • A biaxially stretched polymer film, its preparation method and application

    CN106166882B

  • Method for improving adhesive power of ink in plastic prints

    CN106397815A

  • Multilayer composite membrane adopting XAYBX structure as well as preparation method and application of multilayer composite membrane

    CN107031156A